2010
DOI: 10.1017/s0956793309990136
|View full text |Cite
|
Sign up to set email alerts
|

Wire Fences in Colonial Australia: Technology Transfer and Adaptation, 1842–1900

Abstract: After reviewing the development of wire fencing in Great Britain and the United States of America in the early nineteenth century,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Both were common and widespread before the increasing adoption of iron wire from the 1850s. 17 They were simple lines of branches and logs cleared off the land and piled up to form crude but cost-effective fences. Sand and plant debris accumulated among the tangled branches inside these fences, making perfect rabbit harbour.…”
Section: Brush and Log Fences And Hedgesmentioning
confidence: 99%
“…Both were common and widespread before the increasing adoption of iron wire from the 1850s. 17 They were simple lines of branches and logs cleared off the land and piled up to form crude but cost-effective fences. Sand and plant debris accumulated among the tangled branches inside these fences, making perfect rabbit harbour.…”
Section: Brush and Log Fences And Hedgesmentioning
confidence: 99%
“…Even with the new materials, however, fencing was an expensive business. A five‐strand fence around one square mile of 640 acres (259 ha) took 20 miles (32 km) of wire, which weighed about seven tonnes (Pickard, ). For selectors, fences were often part of their lease conditions and helped prevent stock from straying.…”
Section: Evaluating the Commonsmentioning
confidence: 99%
“…Investigations at Boro Creek (Erskine and Melville, 1984) and Jerrabomberra Creek (Wasson et al, 1998) found fence lines and other European artefacts within sandy overbank deposits. Wire fences were not available in this region until the AD 1860s and not widely used until the AD 1880s (Hancock, 1972;Pickard, 2007Pickard, , 2010, meaning gully erosion and PSA deposition at Boro and Jerrabomberra Creeks could not have occurred as early as at Ryries Creek, Groves Creek or WP5 from Mulwaree River in the early AD 1800s. Rather, PSA deposition in these creeks was likely concurrent with deposition at Gooromon Ponds and Birchams Creeks in the late AD 1800s to the early AD 1900s (Figure 5).…”
Section: Chronology Of Gully Erosion In the Tablelandsmentioning
confidence: 99%